If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11x + -193 + -2x = 119 Reorder the terms: -193 + -11x + -2x = 119 Combine like terms: -11x + -2x = -13x -193 + -13x = 119 Solving -193 + -13x = 119 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '193' to each side of the equation. -193 + 193 + -13x = 119 + 193 Combine like terms: -193 + 193 = 0 0 + -13x = 119 + 193 -13x = 119 + 193 Combine like terms: 119 + 193 = 312 -13x = 312 Divide each side by '-13'. x = -24 Simplifying x = -24
| 29=r-64 | | -9=t+16 | | -95+12x-3x=49 | | -6x+13=5(x-3)-5 | | p-3=-5 | | -5=f+10 | | 10x=159 | | -157+2x-12x=103 | | 6z+6=126 | | -128+7x-13x=70 | | 10x-48-13x=24 | | 4y^9=6 | | -6x-43+2x=33 | | 58-2x=7x+19 | | -196+2x+12x=140 | | -13x-118-5x=206 | | 6-9x=82-23x | | -10x-95+3x=73 | | 5(n-1)=1 | | 2x+5+4x=60 | | (60+x)*0.1=8 | | 100/3=x | | (60+x)*0.1=6 | | 100/3=33,33 | | (60+x)*0.9=6 | | a^2+12a=-36 | | (60+x)*0.9=(6+x) | | y=9x+22 | | 60+x=0.9*(6+x) | | 15x^2+19x+5=7x+8x^2 | | (0)=4x+6 | | 49x^2-25y^2+0=0 |